MOM4p1-TOPAZ data used in the manuscript entitled "On Mode Water formation and erosion in the Arabian Sea: Forcing mechanisms, regionality, and seasonality". - Font, Estel; Vinayachandran, P. N. (University of Gothenburg, 2025)
MOM4p1-TOPAZ data used in the analysis in the manuscript entitled "On Mode Water formation and erosion in the Arabian Sea: Forcing mechanisms, regionality, and seasonality".

The data file contains potential temperature, salinity, and oxygen data from the model run between 2000-2022, 0.25x0.25 degree resolution, of the upper 250m in the Arabian Sea (0-30 N, 35-80 E). The file also contains conservative temperature, absolute salinity, and potential density derived using the GSW toolbox (McDougall et al., 2011).

Refereneces

McDougall, T.J. and P.M. Barker, 2011: Getting started with TEOS-10 and the Gibbs Seawater (GSW) Oceanographic Toolbox, 28pp., SCOR/IAPSO WG127, ISBN 978-0-646-55621-5.

Acknowledgements: The MOM4p1-TOPAZ runs were carried out on the Param Pravega supercomputer at SERC, Indian Institute of Science, Bengaluru. Thanks to GFDL for providing the source code of the coupled physical–ecosystem model (MOM4P1-TOPAZ). The authors thank P. Neema for subsetting the MOM4p1-TOPAZ dataset.
Keywords: Arabian Sea; MOM4p1-TOPAZ; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser